2018
DOI: 10.1111/eth.12727
|View full text |Cite
|
Sign up to set email alerts
|

Predator occurrence and perceived predation risk determine grouping behavior in guanaco (Lama guanicoe)

Abstract: Grouping behavior of social ungulates may depend on both predator occurrence and perceived predation risk associated with habitat structure, reproductive state, and density of conspecifics. Over 3 years, we studied grouping behavior of guanaco (Lama guanicoe) families in Chilean Patagonia during the birthing season and determined their response to variation in predator occurrence and perceived predation risk (habitat structure, calf/adult rate, and density of conspecifics). We considered the effect of two pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…Predation risk is unlikely to explain the variability in spatial distribution among individual belugas, groups of adults, and groups with calves. As observed in other species (Heithaus and Dill 2002;Mumma et al 2017;Iranzo et al 2018), we expected the more vulnerable groups to avoid areas of high predation risk. The main predators of belugas are killer whales (Orcinus orca (Linnaeus, 1758)), polar bears (Ursus maritimus Phipps, 1774), and humans (O'Corry-Crowe 2018).…”
Section: Predation Risk Hypothesismentioning
confidence: 64%
“…Predation risk is unlikely to explain the variability in spatial distribution among individual belugas, groups of adults, and groups with calves. As observed in other species (Heithaus and Dill 2002;Mumma et al 2017;Iranzo et al 2018), we expected the more vulnerable groups to avoid areas of high predation risk. The main predators of belugas are killer whales (Orcinus orca (Linnaeus, 1758)), polar bears (Ursus maritimus Phipps, 1774), and humans (O'Corry-Crowe 2018).…”
Section: Predation Risk Hypothesismentioning
confidence: 64%
“…For instance, Moll et al ( 2016 ) reported that herd size in several African ungulate species depends on predator hunting mode and duration of predation risk. However, vigilance and herd size are not always directly related, as they also depend on other factors affecting individual risk such as reproductive status (Li et al, 2012 ), sex (Barnier et al, 2016 ; Benoist et al, 2013 ), offspring presence (Blanchard et al, 2017 ; Lashley et al, 2014 ), intraspecific competition (Biggerstaff et al, 2017 ; Fattorini et al, 2018 ), habitat features (Pays et al, 2012 ), cover and visibility (Iranzo et al, 2018 ; Pays et al, 2012 ), prey foraging strategy (Creel et al, 2014 ), and predator presence (Iranzo et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with results for mother‐calf pairs in other delphinids, including dusky (Markowitz, 2004) and Guiana ( Sotalia guianensis ) dolphins (Lunardi & Ferreira, 2014), as well as for groups with offspring in different mammalian taxa, e.g., common elands, Taurotragus oryx (Underwood, 1981) and blue wildebeest, Connochaetes taurinus (Lewis & Pusey, 1997). This decreased interindividual proximity provides increased predator protection (Iranzo et al, 2018; Sucunza et al, 2015) and care for the calves (Markowitz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…wildebeest, Connochaetes taurinus (Lewis & Pusey, 1997). This decreased interindividual proximity provides increased predator protection (Iranzo et al, 2018;Sucunza et al, 2015) and care for the calves (Markowitz, 2004).…”
Section: Proportion Of Calvesmentioning
confidence: 99%